Динаміка робочого середовища вібраційних машин об’ємної обробки - Стоцько, З. А.; Сокіл, Б. І.; Топільницький, В. Г. (Видавництво Державного університету "Львівська політехніка", 2000)
In this activity the mathematical model of the vibrational machine of volumetric handling of details is adduced. The system of differential equations of motion of model of a medium for not resonance and resonance cases and also the solution is adduced.